2021
DOI: 10.1002/jac5.1416
|View full text |Cite
|
Sign up to set email alerts
|

Reimbursement outcomes of a pharmacist‐physician co‐visit model in a Federally Qualified Health Center

Abstract: BackgroundPharmacists have demonstrated a positive impact in providing patient care in ambulatory settings. Pharmacists have faced multiple barriers to reimbursement, especially in a Federally Qualified Health Center (FQHC) setting. A commonly cited barrier is lack of recognition as providers under Medicare.ObjectivesThe objective of this study was to describe the reimbursement potential, physician appointment capacity, and billing levels with the use of a pharmacist‐physician co‐visit model in an urban FQHC.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…An example of this is a recently published article which described the reimbursement potential, physician appointment capacity, and billing levels with the use of a pharmacist-physician co-visit model in a Federally Qualified Health Center (FQHC) in Indianapolis, Indiana. 11 The investigators found that with a pharmacist and physician co-visit model, reimbursement was significantly higher compared to physician visits alone ($850 vs. $558 per half-day in clinic). On the other hand, results from a 2020 article evaluating pharmacist reimbursement for independent visits in two Oregon patient-centered medical homes found an average reimbursement rate of $36 per This study, by contrast, demonstrates that reimbursement rates may be significantly higher in states with payment parity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of this is a recently published article which described the reimbursement potential, physician appointment capacity, and billing levels with the use of a pharmacist-physician co-visit model in a Federally Qualified Health Center (FQHC) in Indianapolis, Indiana. 11 The investigators found that with a pharmacist and physician co-visit model, reimbursement was significantly higher compared to physician visits alone ($850 vs. $558 per half-day in clinic). On the other hand, results from a 2020 article evaluating pharmacist reimbursement for independent visits in two Oregon patient-centered medical homes found an average reimbursement rate of $36 per This study, by contrast, demonstrates that reimbursement rates may be significantly higher in states with payment parity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies evaluate the value of a pharmacist from the perspective of quality improvements or study the pharmacist's value only in the context of shared appointments with other healthcare providers. An example of this is a recently published article which described the reimbursement potential, physician appointment capacity, and billing levels with the use of a pharmacist‐physician co‐visit model in a Federally Qualified Health Center (FQHC) in Indianapolis, Indiana 11 . The investigators found that with a pharmacist and physician co‐visit model, reimbursement was significantly higher compared to physician visits alone ($850 vs. $558 per half‐day in clinic).…”
Section: Discussionmentioning
confidence: 99%
“…CMM expands upon the medication optimization practices within MTM primarily by standardizing the process for optimizing medications and working with other members of the interdisciplinary team to ensure that each medication has an appropriate indication, is effective for the condition, can help in achieving clinical goals, is safe, and the patient can adhere to the regimen 6 . Because of CMM's documented positive impact in improving patient outcomes, FQHCs have been including CMM services in the care for their patients, especially for diseases which require more complicated medication regimens like diabetes mellitus 7‐11 . Accompanying this transition to patient‐centered CMM, is a growing push to apply the recommendations of the IOM and Healthy People 2030 to integrate SDOH into all aspects of the pharmacy workflow 5 .…”
Section: Integration Of Social Determinants Of Health Into Comprehens...mentioning
confidence: 99%
“…6 Because of CMM's documented positive impact in improving patient outcomes, FQHCs have been including CMM services in the care for their patients, especially for diseases which require more complicated medication regimens like diabetes mellitus. [7][8][9][10][11] Accompanying this transition to patient-centered CMM, is a growing push to apply the recommendations of the IOM and Healthy People 2030 to integrate SDOH into all aspects of the pharmacy workflow. 5 Prominent examples of this integration of responses to SDOH can be found within various pharmacy practice settings.…”
Section: Integration Of Social Determinants Of Health Into Comprehens...mentioning
confidence: 99%
“…Despite the potential benefits of shared visit and split-shared visit models, a review of the literature only found four publications discussing the outcomes of such practice models in the FQHC or Rural Health Center (RHC) setting, which summarized outcomes from seven different health centers. 13 - 16 There are currently 1385 registered FQHCs 17 and 4799 RHCs 18 in the United States.…”
Section: Introductionmentioning
confidence: 99%